Constituição da identidade de cursos de licenciatura em matemática à luz da modernidade líquida - Junqueira, Sonia Maria da Silva (2010)
Facet to the uncertainties and demands of the contemporary world, the training of teachers of mathematics has a place of intense debate and research. This study points to the solidified aspects that constitute the identity of Courses in Mathematics, including those that occurred after contemporary reforms in education. So, Bauman's liquid modernity represents the ideal setting for recognition of solidification and flow that we are searching for. It developed an documentary analysis in an investigative approach which appealed to fragments of the historical process of teaching of mathematics in Brazil, movements that searched for changes, legislation relevant to graduate programs, and pedagogical projects of two higher education institutions: Federal University of Mato Grosso (UFMT) and Catholic University of São Paulo (PUC-SP). The complex attempt to identify elements that make the identity of Mathematics Courses for teachers allowed us to recognize that the "identity", is flexible and fluid, as well as revealing the presence of "solid", "solid melting" and "liquids." Was identified, through the analysis, four dimensions of identity: reflective, individual, communitarian and organizational dimensions, designed as provisional and inconclusive in characterizing the identity of the Mathematics Courses for teachers. The reflexive dimension of identity reveals the necessity of interaction and integration between different knowledge set. The individual dimension of identity establishes in individual choices, where the person forms at the same time that is formed by the same group that form. Normalizing and guiding mechanisms reveal organizational dimension of identity. The communitarian dimension of identity allows us to understand that the made choices or choices directed by a group are relevant in establishing the identity sought. It is also considered that new dimensions of identity can be recognized in the constant motion of the identified dimensions